Impact of Green Banking Implementation, Financial Performance, and Covid-19 Crisis on Islamic Bank Profitability in Indonesia - Ramdani, Ramdani; Mawardi, Imron; Sulaeman, Sulaeman (International Journal of Islamic Economics and Finance (IJIEF), 2023)
The purpose of this research is to test empirically the impact of green banking implementation, financial performance, and Covid-19 crisis on Islamic bank profitability in Indonesia for the period of 2015-2021. This study uses two quantitative approaches, specifically static panel data method and dynamic panel data method (generalized method of moments or GMM). The secondary data used in this paper with a total sample of 10 Islamic commercial banks in Indonesia. This study finds that the implementation of Green Banking as the main determinant has a significant relationship to the profitability of Islamic Banks in Indonesia. The study also finds that financial performance variables such as CAR, NPF, and OEF show that contribution to the level of Islamic bank profitability in Indonesia. Further, other finding regarding the dummy crisis variable, Covid-19 crisis finds that a strong relationship to the Islamic bank profitability. It means that Covid-19 crisis will impact negatively to Islamic bank profitability in Indonesia. Based on the results of the robustness check, the model in this research is stated to be robust. The findings are expected to be useful for policy makers as well as for Islamic banking circles. Research results can be used as input in formulating policies in achieving sustainable development goals and economic and social recovery programs after the Covid-19 pandemic.